Modified lignocellulose and rich starch for complete saccharification to maximize bioethanol in distinct polyploidy potato straw. (1st August 2021) - Madadi, Meysam; Zhao, Kanglu; Wang, Youmei; Wang, Yanting; Tang, Shang-wen; Xia, Tao; Jin, Nengzhou; Xu, Zhijun; Li, Guanhua; Qi, Zhi; Peng, Liangcai; Xiong, Zhiyong
Graphical abstract: Highlights: Desirable ploidy potato straw is rich in soluble sugars, starch and lignocellulose. Complete saccharification of starch and lignocellulose achieved in potato straw. Two minimized mild pretreatments are sufficient for biomass saccharification. Maximum bioethanol yield achieved in the desirable polyploidy potato straw. A powerful strategy for cost-effective ethanol production with minimum wastes release. Abstract: Potato is a major food crop with enormous biomass straw, but lignocellulose recalcitrance causes a costly bioethanol conversion. Here, we selected the cytochimera (Cyt) potato samples showing significantly-modified lignocellulose and much increased soluble sugars and starch by 2–4 folds in mature straws. Under two pretreatments (8 min liquid hot water; 5% CaO) at minimized conditions, the potato Cyt straw showed complete enzymatic saccharification. Further performing yeast fermentation with all hexoses released from soluble sugars, starch and lignocellulose in the Cyt straw, this study achieved a maximum bioethanol yield of 24 % (% dry matter), being higher than those of other bioenergy crops as previously reported. Hence, this study has proposed a novel mechanism model on the reduction of major lignocellulose recalcitrance and regulation of carbon assimilation to achieve cost-effective bioethanol production under optimal pretreatments. This work also provides a sustainable strategy for utilization of potato straws with minimum waste release.